2018
DOI: 10.1242/dev.154583
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical genetic interactions between FOXG1 and LHX2 regulate the formation of the cortical hem in the developing telencephalon

Abstract: During forebrain development, a telencephalic organizer called the cortical hem is crucial for inducing hippocampal fate in adjacent cortical neuroepithelium. How the hem is restricted to its medial position is therefore a fundamental patterning issue. Here, we demonstrate that Foxg1-Lhx2 interactions are crucial for the formation of the hem. Loss of either gene causes a region of the cortical neuroepithelium to transform into hem. We show that FOXG1 regulates Lhx2 expression in the cortical primordium. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 25 publications
6
45
0
Order By: Relevance
“…2e, Extended Data Fig. 1); this pattern precisely recapitulates the endogenous Lhx2 expression 26,27 . These early RGs showed characteristic radial fibers and end-feet at the ventricle surface; the position of their soma likely reflected the stage of cell cycle progression, including those dividing at the ventricle surface ( Fig.…”
Section: Probing the Diversity Of Rgsmentioning
confidence: 55%
“…2e, Extended Data Fig. 1); this pattern precisely recapitulates the endogenous Lhx2 expression 26,27 . These early RGs showed characteristic radial fibers and end-feet at the ventricle surface; the position of their soma likely reflected the stage of cell cycle progression, including those dividing at the ventricle surface ( Fig.…”
Section: Probing the Diversity Of Rgsmentioning
confidence: 55%
“…Here, by overexpression of Foxg1 in the hem from E10.5 onwards, we detected a cell fate switch of the hem-derived CR cells to dentate granule neurons, accompanied with ectopic expression of Lhx2. Previous study has reported that loss of Foxg1 leads to a reduction of Lhx2 expression, and Foxg1 can directly bind to Lhx2 locus [ 16 ]. In this study, we demonstrated that forced expression of Foxg1 is sufficient to induce Lhx2 expression in the hem.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that forced expression of Foxg1 is sufficient to induce Lhx2 expression in the hem. It has been reported that Lhx2-expressing cells can be specified into hippocampal cells and this only happens in tissues adjacent to the hem [ 16 ]. Here, induced expression of Lhx2 in our transgenic mice may be responsible for the transformation of CR cells to their granular fate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations